The role of the higher boards of financial oversight and accounting in light of the widespread phenomena of political and institutional division (Sebha University Conference Proceedings, 2022)
This study sought to shed light on the role of the Libyan Audit Bureau in light of political and institutional schisms, specifically in the context of the Libyan Audit Bureau's advisory and evaluation role, The Bureau has attempted to fill some of the political and institutional voids left by the schisms by urging the subject entities to enact emergency exceptional measures that take the public interest into account. However, despite the Bureau's efforts to reduce corruption and tighten control over various state institutions, the Bureau's efforts have had limited impact due to the spread of institutional schisms and the multiplicity of authorities within the state. For example, the increase in the expenditure indicators in Chapter One by rates exceeding 38% of the total budget, and the resulting inflation in the number of employees in the public sector despite the adoption by the Audit Bureau of many initiatives aimed at institutional development and supporting liaison and communication mechanisms with various stakeholder groups. To achieve the anticipated impact of the Libyan Audit Bureau's role, the study recommended immediate unifying of the institution, ensuring internal stability, and distancing it from political strife. The Bureau must also work to raise awareness among the various stakeholder groups about the nature of the challenges confronting subject entity reform and institutional development, as well as what they must do during this stage. In addition, there is a need for the Bureau to seek to frame governance principles through legislation and bind subject entities to them.